Jerusalem artichoke (Helianthus tuberosus L.) as a medicinal plant and its natural products - Sawicka, Barbara; Skiba, Dominika; PszczóÅ‚kowski, Piotr; Aslan, Imran; Sharifi"Rad, Javad; Krochmal-Marczak, Barbara (Cellular and Molecular Biology, 2020)
Identifying the nutritional and health properties of Helianthus tuberosus, and learning more about this valuable species. It is believed that increased consumption of Jerusalem artichoke (JA) products is related to low blood pressure. One of many questions to answer is whether supplementation of inulin and inulin derivatives obtained from Helianthus tuberosus tubers and aerial parts can be used as antidiabetic, anti-carcinogenic, anti-fungistatic, anti-constipation, body mass-reducing, metabolism-improving agents. We ran a search in Medline, Web of Science, Scopus, Agricola, EBSCO - Food Science Source, Europe PMC, PBL, Cochrane Central Register of Controlled Trials until March 2020. We also browsed reference lists of articles and previous reviews. No language limitations were applied. Jerusalem artichoke (JA) has multiple applications thanks to its rich chemical composition, resistance to biotic and abiotic factors, as: functional food, bioactive ingredient, raw material for the production of ethanol and butanol, succinic, citric and lactic acid. It can be used in medicine and the pharmaceutical industry, because it contains anti-fungistatic, anti-carcinogenic and antioxidant components, and the production of the raw material is easy and inexpensive. It also lowers high cholesterol, triglycerides and high glucose levels; facilitates weight loss; detoxes the organism (e.g. alcohol, heavy metals, radionuclides); lowers uric acid levels; has immunostimulating properties; protects the gastric mucosa, prevents constipation; prevents acne; improves metabolism in lipid disorders; reduces body mass; has cytotoxic properties in breast cancer. It also helps in cardiovascular diseases, chronic infectious diseases; chronic fatigue syndrome; gut flora disorders; immune system disorders. A number of Jerusalem artichoke-derived products were discussed.